Evaluation of pulmonary tuberculosis case detection improvement with the deployment of XpertMTB/Rif in the tuberculosis control program of cross River State, Nigeria - Ernest Afu Ochang; Ubleni E Emanghe; Atana Ewa; Akaninyene Otu; Jonah B Offor; Micheal Odo; Aniekan Etokidem; Barinadaa Afirima; Oju Eni Owuna; Sunday M Obeten; Martin M Meremikwu (International Journal of Mycobacteriology, 2017)
Objective/Background: Global indices show that Nigeria has the highest tuberculosis (TB)-related mortality rate. Overdependence on Ziehl–Neelsen (ZN) smear microscopy for diagnosis and human immunodeficiency virus (HIV)/AIDS has limited control efforts. The new polymerase chain reaction-based XpertMTB/Rif (Cepheid Inc., CA, USA), which detects Mycobacterium tuberculosis and rifampicin resistance, was introduced in Cross River State in 2014. We evaluated the increment in pulmonary TB case detection following introduction of XpertMTB/Rif into the Cross River State TB control program. Materials and Methods: Data from three XpertMTB/Rif centers in Cross River were prospectively collected from June 2014 to December 2015. One spot specimen and one early morning sputum specimen were collected from each patient and tested using microscopy while one specimen was used for XpertMTB/Rif. Results: A total of 2326 patients comprising 47.4.0% (1103) males and 52.6% (1223) females were evaluated. Their mean age was 38.8 years (range 4–89 years); 42.6% (991) were HIV positive and 50.9% (1183) HIV negative, and for 6.5% (158) HIV status was unknown. XpertMTB/Rif detected M. tuberculosis in 22.9% (534) of patients, while 16.8% (391) were ZN smear positive. Smear microscopy missed 24.5% (131/534) of cases (P < 0.0001). When patients where categorized according to HIV status, XpertMTB/Rif detected 23.7% (280/1183) and ZN smear microscopy detected 18.5% (219/1183) of HIV-negative patients. XpertMTB/Rif detected 21.5% (213/991) and ZN smear 14.1% (140/991) of HIV-positive patients. TB case detection was significantly higher in HIV-negative patients than in HIV-positive patients when either XpertMTB/Rif and/or ZN was used (P = 0.018 and 0.012, respectively). Conclusion: The use of XpertMTB/Rif has significantly increased TB case detection and data in Cross River State. Scale-up of additional strategies such as culture is still required to improve TB detection in HIV patients.